Peptide modulators of alpha‐glucosidase. Issue 6 (29th April 2015) - Roskar, Irena; Molek, Peter; Vodnik, Miha; Stempelj, Mateja; Strukelj, Borut; Lunder, Mojca
<x xml:space="preserve">Abstract</x> In this study, screening of peptide libraries was used to select peptides with affinity towards mammalian intestinal alpha glucosidase as potential leads in antidiabetic agent development. Two linear and two cyclic heptapeptides with high affinity towards intestinal alpha glucosidase were selected and were further shown to compete for enzyme binding site with known inhibitors acarbose and voglibose. Modulatory peptides (both cyclic peptides inhibited while both linear peptides increased enzyme activity) represent promising leads for development of efficient alpha glucosidase inhibitors. <boxed-text content-type="graphic" id="jdi12358-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>